Evaluating Student Cultural Competence in an Associate in Science in Nursing Program. - Chen, Hsiu-Chin; Jensen, Francine; Measom, Gary; Nichols, Nyree Dawn (Teaching & Learning in Nursing, 2018)
The purpose of this study was to evaluate student development of cultural competence over time and to identify factors that influence the development of cultural competence in an associate in science in nursing (ASN) program. This longitudinal quantitative study used a pretest and posttest survey to collect data on 145 ASN students' cultural competence. The results indicated that students performed at a culturally competent level. The predictor of cultural encounters contributed approximately 58.5% of the variance in cultural competence.